Distribution of lymphocele following lymphadenectomy in patients with gynecological malignancies - Soo Youn Song; Mia Park; Byung Hun Kang; Jung Bo Yang; Young Bok Ko; Mina Lee; Ki Hwan Lee; Heon Jong Yoo (Korean Society of Obstetrics and Gynecology, 2020)
Objective This study identified the distribution of lymphocele, as well as the factors associated with lymphocele formation, in patients undergoing pelvic and/or para-aortic lymph node dissection (PLND and/or PALND) for gynecologic malignancies. Methods This study was retrospective, and data were collected from patients who underwent surgical procedures including lymphadenectomy due to gynecologic malignancies from March 2013 to May 2016. Lymphocele was defined by postoperative computer tomography within 2 weeks after surgery. Results A total of 116 patients underwent lymphadenectomy, of whom, 47 (42.0%) developed lymphocele and 14 (12.1%) had symptomatic lymphocele formation. The affecting factors of lymphocele formation were PLND concomitant with PALND and a large amount of blood loss ≥600 mL (P=0.030 and P=0.006, respectively). All clinical factors were not significantly different between patients with symptomatic and asymptomatic lymphocele. Lymphocele developed more frequently in the left side (67.1%) of the body compared to the right side (48.7%), and in the pelvic area (75.9%) compared to the para-aortic area (24.1%, P<0.001, both). Conclusion Lymphocele formation is more prevalent in the left and pelvic area of the body compared to the right and paraaortic side. PLND concurrent with PALND and large amounts of blood loss were significant risk factors for lymphocele formation.